2019
DOI: 10.1017/s0014479719000309
|View full text |Cite
|
Sign up to set email alerts
|

Importance of phosphorus and potassium in soil-specific nutrient management for wet-season rice in Cambodia

Abstract: Rice is widely grown in rainfed lowlands during the wet season in the Mekong region. Limited nutrient availability is a common constraint on crop yield, and the optimal rate of fertilizer application depends on the soil type. The objective of our study was to evaluate rice productivity and the economic feasibility of various nutrient management regimes in Cambodia. We conducted field experiments on three soil types (Prey Khmer, Prateah Lang, and Toul Samroung, equivalent to Psamments, Plinthustalfs, and Endoaq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…For those farmers willing to invest more in dry-season rice cultivation on Toul Samroung soil, adding N and K to the soil-specific recommendation would slightly increase productivity without reducing profits. For wet-season rice, in contrast, we previously showed that additional fertilizer inputs into soil-specific management significantly and consistently improved profits (Kong et al, 2019). There could be three reasons for the different implications of the nutrient requirements between dry-and wet-season rice.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…For those farmers willing to invest more in dry-season rice cultivation on Toul Samroung soil, adding N and K to the soil-specific recommendation would slightly increase productivity without reducing profits. For wet-season rice, in contrast, we previously showed that additional fertilizer inputs into soil-specific management significantly and consistently improved profits (Kong et al, 2019). There could be three reasons for the different implications of the nutrient requirements between dry-and wet-season rice.…”
Section: Discussionmentioning
confidence: 86%
“…One is that the growth duration is much shorter in non-photoperiod-sensitive cultivars in the dry season than in photoperiod-sensitive cultivars in the wet season. The other is that the recommended rates for dry-season rice (Table 3) are much higher than those for wet-season rice (57-63 kg ha −1 of N, 23-38 kg ha −1 of P 2 O 5 , and 0-35 kg ha −1 of K 2 O on Toul Samroung and Prateah Lang soils; Kong et al, 2019), reflecting the fact that farmers apply more fertilizer in the dry season than in the wet season, particularly N and P (Fukai and Ouk, 2012). In addition, the frequent loss of standing water in wet-season rice, usually grown under rain-fed lowland conditions, might accelerate the N loss through denitrification or leaching (Buresh et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Leaching of N and other nutrients may also limit productivity of these soils. The Prey Khmer soil in Cambodia has low potential productivity for wetland rice even following recommended rates of fertilizer application [12,54,55].…”
Section: Lowland Sands: Chemical and Physical Characteristics And Deg...mentioning
confidence: 99%